1993
DOI: 10.1037/0012-1649.29.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Inducing children to generate mnemonic organizational strategies: An examination of long-term retention and materials.

Abstract: Whether children's strategy transfer is influenced by prior experience was investigated in a memory context. Specifically, experience with highly related materials was predicted to facilitate subsequent use of organizational strategies and recall of low-associated items. In Experiment 1, 3rd graders induced to use organizational strategies through exposure to categorical materials demonstrated better recall and organization, both immediately and 3-5 days later, than children explicitly trained in strategy use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(64 reference statements)
0
4
0
2
Order By: Relevance
“…Research using a variety of materials (e.g., categorized words, texts) has consistently demonstrated that children with more detailed knowledge of the to-beremembered information recall that information better and typically implement strategies more effectively than children with less detailed knowledge (e.g., Best 1993;Bjorklund and Zeman 1982;Schneider 1986;). …”
Section: Factors Affecting Children's Strategy Use and Developmentmentioning
confidence: 99%
“…Research using a variety of materials (e.g., categorized words, texts) has consistently demonstrated that children with more detailed knowledge of the to-beremembered information recall that information better and typically implement strategies more effectively than children with less detailed knowledge (e.g., Best 1993;Bjorklund and Zeman 1982;Schneider 1986;). …”
Section: Factors Affecting Children's Strategy Use and Developmentmentioning
confidence: 99%
“…Transfer differs among cognitive domains (Brown, 1990) and is affected by factors like metacognition (Alexander, Carr, & Schwanenflugel, 1995). Transfer has been measured in a variety of tasks, for instance, memory strategies, where considerable individual and age differences have been found (Best, 1993; Block, 1993). It can be concluded that empirical indicators for the model's parameters can be found, although it is unlikely that the parameters can be reduced to single psychological variables.…”
Section: From Basic Principles To a Dynamic Systems Modelmentioning
confidence: 99%
“…There are an increasing number of positive findings that suggest that training in strategy usage can be adapted to suit both strategic and cognitive limitations in young and impaired children [67,74,75] just as strategies can be adapted to benefit adults with learning difficulties [76,77]. Where executive deficits limit strategic use of working memory, external cues to implement a strategy may lead to functional improvement or executive and planning abilities could themselves be the primary target for rehabilitation efforts [78,79].…”
Section: The Development Of Strategy Usagementioning
confidence: 99%